Using recruitment and selection to build a primary care workforce for the future. Issue 3 (4th May 2019) - Brown, Celia; McManus, Chris; Davison, Ian; Gill, Paramjit; Lilford, Richard
ABSTRACT: Recruitment and selection are critical components of human resource management. They influence both the quantity and quality of the healthcare workforce. In this article, we use two different examples of primary care workers, General Practitioners in the UK and Community Health Workers in low- and middle- income countries, to illustrate how recruitment and selection are, and could be, used to enhance the primary care workforce in each setting. Both recruitment and selection can be costly, so when funding is limited, decisions on how to spend the human resources budget must be made. It could be argued that human resource management should focus on recruitment in a seller's market (an insufficient supply of applicants) and on selection in a buyer's market (sufficient applicants but concerns about their quality). We use this article to examine recruitment and selection in each type of market and highlight the interactions between these two human resource management decisions. Recruitment and selection, we argue, must be considered in both types of market; particularly in sectors where workers' labour impacts upon population health. We note the paucity of high-quality research in recruitment and selection for primary care and the need for rigorous study designs such as randomised trials.